The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1074/jbc.m110.208496
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Batrachotoxin-sensing Residues in Segment IIIS6 of the Sodium Channel

Abstract: Ion permeation through voltage-gated sodium channels is modulated by various drugs and toxins. The atomistic mechanisms of action of many toxins are poorly understood. A steroidal alkaloid batrachotoxin (BTX) causes persistent channel activation by inhibiting inactivation and shifting the voltage dependence of activation to more negative potentials. Traditionally, BTX is considered to bind at the channel-lipid interface and allosterically modulate the ion permeation. However, amino acid residues critical for B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 59 publications
(49 reference statements)
3
54
0
Order By: Relevance
“…However, these toxins do not bind to the outer pore but instead to the inner pore (BTX) (48)(49)(50) or to other transmembrane helices (PTX-B) (47,51). Thus, although overall Na + channel structure in L. epinephelus likely is influenced by multiple prey toxins, we are confident that the P-loop replacements we discuss have been shaped by selection from TTX, because the outer pore is the target of TTX, and these functional mutations are at sites critical to TTX binding but uninvolved in BTX or PTX-B binding (47)(48)(49)(50)(51).…”
Section: Resultsmentioning
confidence: 99%
“…However, these toxins do not bind to the outer pore but instead to the inner pore (BTX) (48)(49)(50) or to other transmembrane helices (PTX-B) (47,51). Thus, although overall Na + channel structure in L. epinephelus likely is influenced by multiple prey toxins, we are confident that the P-loop replacements we discuss have been shaped by selection from TTX, because the outer pore is the target of TTX, and these functional mutations are at sites critical to TTX binding but uninvolved in BTX or PTX-B binding (47)(48)(49)(50)(51).…”
Section: Resultsmentioning
confidence: 99%
“…Mutational studies show that BTX binds in the inner pore, contacts the inner helices from all four repeats (Wang et al, 2006(Wang et al, , 2007a, and may adopt an ion-permeable "horseshoe" conformation within the channel as we recently proposed (Du et al, 2011a). In contrast, pyrethroids including deltamethrin are proposed to bind in the lipid-exposed interface between the linker-helix IIS4-S5, the outer helix IIS5, and the inner helix IIIS6 (O'Reilly et al, 2006;Du et al, 2009).…”
Section: Resultsmentioning
confidence: 80%
“…2A; Supplemental Table S2), that are critical for the action of pyrethroids (Du et al, 2009). In addition, we have shown that Gly 3i14 and Phe 3i16 are also critical for the action of BTX (Du et al, 2011a). To determine whether these residues are also critical for the action of BTG 502, we examined the effect of BTG 502 on these four mutant channels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations